Pengaruh Citra Merek dan Kualitas Produk Terhadap Keputusan Pembelian Body Lotion Nivea di Kecamatan Seberang Ulu II Kota Palembang - Indah Putri Neza, Indah; Puspasari, Mardiana; Herudiansyah, Gumar (PT Maju Malaqbi Makkarana, 2025)
This research aims to determine the influence of brand image and product quality on purchasing decisions for Nivea body lotion in Seberang Ulu II District, Palembang City. The type of research used is associative. The sample used was 100 respondents with a sampling technique using Purposive Sampling. The data used is primary data and secondary data. The data collection method used was through a questionnaire. The data analysis used is quantitative qualitative analysis. The analysis technique used is multiple linear regression. The results of the F test show that the significant influence of brand image and product quality has a positive effect on the decision to purchase Nivea body lotion in Seberang Ulu II District,Palembang City. The results of the partial t-test show that the significant influence of brand image and product quality has a positive effect on the decision to purchase Nivea body lotion in Seberang Ulu II District, Palembang City.